Attitudes of University Students towards People with Disabilities in the Social Context: A Preliminary Study - Azzahrah, Anuar; Nor Mazlina, Ghazali (Faculty of Cognitive Sciences & Human Development UNIMAS, 2015)
The article highlights on the previous literature on the attitudes of college or university students towards people with disabilities in the social context globally. The article also includes factors that influence the willingness of college or university students to build relationship with people with disabilities in the social context (such as friendship, dating, and marriage) and perceptions of students that add to the existing challenges encountered by people with disabilities. When perception is being measured in a more specific dimension, such as, in the social distance context, it provides a practical means to understand people’s awareness towards disability.